Komparasi Pendapatan Peternak Ayam Broiler Pola Mandiri dan Pola Kemitraan di Kabupaten Trenggalek - Ahmad Habibi Walid; Widi Artini; Tutut Dwi Sutiknjo; Nina Lisanty (Universitas Kadiri, 2021)
The partnership in the broiler farming business triggers an increase in the broiler population. It motivates prospective breeders to do broiler farming due to the availability of assistance in terms of capital, management, as well as marketing. However, many prospective breeders believe the rumors that the partnership pattern is not that attractive. The purpose of this study was to determine the differences in the costs and income of the broiler farming business between the independent and partnership pattern business. The study also examined the differences in the feasibility of both patterns in the broiler farming business in Jombok Village, Pule District, Trenggalek Regency. This research utilized a case study method. From the study results, it was known that there was a significant difference in the cost of broiler farming business of both patterns. The cost of broiler farming of the partnership pattern was higher than of the independent pattern. The income of broiler farming of the partnership pattern tended to be smaller than the independent pattern. However, the average return from the partnership pattern broiler business was more significant than the independent pattern. Although the two patterns of broiler farming were feasible, the revenue and cost ratio in the independent broiler farming business was greater than that of the partnership broiler business. It can be concluded that from an economic point of view, broiler farming with an independent pattern was more profitable than a partnership pattern.Â Pola kemitraan pada usaha ternak ayam memicu meningkatnya populasi ayam. Pola kemitraan memotivasi calon peternak untuk melakukan usaha ternak ayam karena ketersediaan bantuan dalam hal modal, manajemen, dan juga pemasaran. Meski demikian, calon peternak banyak yang mempercayai rumor yang beredar yang menyatakan bahwa pola kemitraan tidak semenarik itu. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan biaya dan pendapatan serta kelayakan usaha ternak ayam ras broiler pola kemitraan dan pola mandiri di Desa Jombok, Kecamatan Pule, Kabupaten Trenggalek. Penelitian menggunakan metode studi kasus. Dari hasil penelitian dapat diketahui bahwa terdapat perbedaan biaya yang signifikan pada biaya peternakan ayam ras broiler antara kedua model tersebut. Biaya peternakan ayam ras broiler model kemitraan lebih tinggi daripada model mandiri, dan pendapatan peternakan ayam ras broiler model kemitraan seringkali lebih rendah daripada model mandiri. Namun ratarata pendapatan dengan model kemitraan lebih besar dibandingkan dengan model mandiri. Meskipun kedua jenis model usaha peternakan ayam ras broiler tersebut layak, namun rasio pendapatan dan biaya dari usaha peternakan ayam ras broiler mandiri lebih tinggi dibandingkan dengan usaha broiler kemitraan. Dapat disimpulkan bahwa dari segi ekonomi, peternakan ayam ras broiler mandiri lebih menguntungkan daripada kemitraan.